2011
DOI: 10.1007/s10551-011-0843-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Ethics Research: The Importance of Controlling for the Social Desirability Response Bias

Abstract: gender, social desirability response bias, ethics research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(175 citation statements)
references
References 52 publications
13
146
2
5
Order By: Relevance
“…Robertson and Ross (2003), for example, found that females are more sensitive to CSR activities than males, while Dalton and Ortegren's (2011) study suggests that the greater value attached to CSR by females is the result of response bias and the attempt at social desirability. Given the potential significance of gender in relation to CSR, we tested for familiarity as indicated by responses to the first question and gender (Table 2).…”
Section: Gender and Agementioning
confidence: 94%
“…Robertson and Ross (2003), for example, found that females are more sensitive to CSR activities than males, while Dalton and Ortegren's (2011) study suggests that the greater value attached to CSR by females is the result of response bias and the attempt at social desirability. Given the potential significance of gender in relation to CSR, we tested for familiarity as indicated by responses to the first question and gender (Table 2).…”
Section: Gender and Agementioning
confidence: 94%
“…Gender is one of the most frequently studied variables within the ethics literature and a large number of studies find that females are more ethical than males (Dalton and Ortegren, 2011;O'Fallon and Butterfield, 2005). Females make more ethical judgements (Cole and Smith, 1996;Dawson, 1997;Deshpande et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Sosialisasi awal dipengaruhi oleh imbalan dan biaya yang berhubungan dengan peran-peran dalam pekerjaan. Karena sifat dan pekerjaan yang sedang dijalani membentuk perilaku melalui struktur imbalan, pria dan wanita akan merespon isu-isu etika secara sama dalam lingkungan pekerjaan yang sama (Dalton & Ortegren, 2011). Dengan demikian, pendekatan struktural memprediksi bahwa pria dan wanita dalam pekerjaan yang sudah ada atau dalam pelatihan untuk pekerjaanpekerjaan khusus akan menunjukkan prioritas yang sama.…”
Section: Kerangka Teoritis Dan Pengembangan Hipotesis Kerangka Teoritisunclassified